2013
DOI: 10.1186/1471-2458-13-444
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory illness healthcare-seeking behavior assessment in the Lao People’s Democratic Republic (Laos)

Abstract: BackgroundRespiratory illness (RI) remains a public health problem in Laos, but little is known about the overall burden and people’s healthcare-seeking behavior for RI. Understanding the burden of RI and community patterns of healthcare-seeking behavior would provide better guidance for Lao public health program and policy planners to improve RI public health practice, surveillance systems, and prevention strategies.MethodsA quantitative and qualitative survey was conducted in 14 randomly selected villages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
2
20
1
Order By: Relevance
“…Practices of self-treatment with or without the use of traditional medicines are sometimes completely excluded from studies ( Pillai et al. 2003 ; Mayxay et al. 2013 ) despite the continued evidence that such practices prevail ( Cocks and Dold 2000 ; Mathez-Stiefel et al.…”
Section: Introductionmentioning
confidence: 99%
“…Practices of self-treatment with or without the use of traditional medicines are sometimes completely excluded from studies ( Pillai et al. 2003 ; Mayxay et al. 2013 ) despite the continued evidence that such practices prevail ( Cocks and Dold 2000 ; Mathez-Stiefel et al.…”
Section: Introductionmentioning
confidence: 99%
“…36,[40][41][42][47][48][49][50] . Distance to healthcare facilities is also related to worse health outcomes, especially in rural environments/settings because sick people receive delayed or no medical attention at all 39,[51][52][53][54][55][56][57][58] . Specifically, in the case of rabies, increased distance to a health facility has been associated with a delay in PEP uptake in Dehli and Northwestern Tanzania 59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatments in informal health facilities or by self‐medication are quite common among ILI cases. According to studies involving community surveys on ILI behaviour in some LMICs, about a third to a half of the infected cases sought health care in informal or non‐health facility sectors . The recent systematic review indicated that there was no study estimating the economic burden on patients who are seeking care only outside medical settings.…”
Section: Overall Process Of Economic Burden Estimation For Seasonal Imentioning
confidence: 99%